From passive to active dialogue? : Aboriginal lands, development and métissage in Québec, Canada - Desbiens, Caroline; Rivard, Étienne (cultural geographies, 2016)
Over the last decade, northern Québec (Canada) has been the stage of tremendous changes regarding the active role played by Aboriginal peoples in matters of planning and territorial development. This gradual rise, if incomplete, of the Aboriginal agency greatly impacts, as we shall argue here, on the identities and territorialities of both Aboriginal and non-Aboriginal communities, through new policies, legislation, treaty processes, institutions (public or private) devoted to development, territorial governance or the increasing number of cross-cultural partnerships and investments. The goal of this paper is to offer a critical portrait of the recent changes affecting the relations between Aboriginal and non-Aboriginal communities in northern Québec, and discuss the limits of the cross-cultural dialogue in which they are engaged. This argument is an attempt to show how development and planning are rich grounds for understanding the state and the economy as ontological. It will be illustrated through the recent emergence of the Québec government’s Plan Nord (‘Northern Plan’), an ambitious program of development, and the treaty process involving three Innu First Nations in the regions of Saguenay-Lac-Saint-Jean and Côte-Nord. Conceived of as a dynamic form of cross-cultural dialogue shaped by power relations, the concept of métissage (hybridity) grounds our analysis and highlights the challenges of multicultural territorial planning. If Québec is presently engaging in a renewed cross-cultural dialogue with First Nations, the final result of this dialogue, however, remains uncertain.